1981
DOI: 10.1111/j.1748-1716.1981.tb06723.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high oxygen tension on the metabolism of vasoactive hormones in isolated perfused rat lungs

Abstract: The effect of exposure of rats to high concentrations of oxygen (90-95%, normobaric) on the activation of angiotensin I to angiotensin II and on the inactivation of bradykinin, prostaglandin E2 (PGE2) and 5-hydroxytryptamine (serotonin) in the pulmonary circulation of isolated perfused rat lungs was investigated. After 36 h exposure, PGE2 survival in the pulmonary circulation increased and reached 3 times the control value after 48 h exposure. A decrease in the conversion of angiotensin I to angiotensin II was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…105,108,109 Harabin et al demonstrated that prolonged exposure to an F IO 2 of 1.0 decreases endothelial metabolism by 50% in dogs. 105 This accounts for pulmonary dysregulation of circulating vasoactive substances during hyperoxia 110 and partially explains subsequent pre-terminal hemodynamic instability. 105 Physiologic states associated with increased metabolism are known to enhance HALI, 79 probably because of elevated oxidative phosphorylation and increased mitochondrial ROS production.…”
Section: Overview Of the Molecular Biology Of Halimentioning
confidence: 99%
“…105,108,109 Harabin et al demonstrated that prolonged exposure to an F IO 2 of 1.0 decreases endothelial metabolism by 50% in dogs. 105 This accounts for pulmonary dysregulation of circulating vasoactive substances during hyperoxia 110 and partially explains subsequent pre-terminal hemodynamic instability. 105 Physiologic states associated with increased metabolism are known to enhance HALI, 79 probably because of elevated oxidative phosphorylation and increased mitochondrial ROS production.…”
Section: Overview Of the Molecular Biology Of Halimentioning
confidence: 99%
“…After exposure of rats to greater than 95% 0, for 50 h, pulmonary capillary surface area decreases to less than 25% of control [2]. Toivanen, Hartiola, and Bakhle [18] found a reversible decrease in conversion of angiotensin I to angiotensin 11 in isolated perfused lungs from rats exposed to hyperoxia for 48 h. Dobuler, Catravas, and Gillis [19] detected even earlier changes in lung ACE activity in rabbits exposed to hyperoxia in vivo. They reported a small but significant reduction in rabbit lung 3H-benzoyl-Phe-Ala-Pro hydrolysis after a 16-h oxygen exposure.…”
Section: Mk351a Binding Assaymentioning
confidence: 97%
“…Lung ACE activity decreases during hyperoxia exposure before any ultrastructural change is detected in the lung microvasculature [18,191. Hyperoxia causes cytopathic changes in lung endothelial cells and destruction of about 50% of lung capillaries after 3 days of oxygen exposure.…”
Section: Mk351a Binding Assaymentioning
confidence: 99%
“…The early onset of this deficiency, 2h after treatment, suggests that it may be related to the early leukopaenia which results from sequestration of activated leukocytes in the pulmonary circulation. The activity of PGDH is readily inhibited by a hyperoxic environment (Parkes & Eling, 1975;Klein et al, 1978;Chaudhari et al, 1979;Toivonen et al, 1981) and the generation of oxygen-derived free radicals by activated leukocytes (Freeman & Crapo, 1982;Schraufstatter et al, 1984) may similarly serve to inactivate PGDH.…”
Section: Discussionmentioning
confidence: 99%